Risk Management of Non-bank Home Ownership Financing - Fadhilah Hasib, F; Firrizqi, A; Afiqoh, L (KnE Social Sciences, 2019)
The Ministry of Public Works and Housing through General Directorate of Housing Financing (2016) estimated that housing demand by 2025 will reach more than 30 million units, so that this demand of new housing estimated will reach 1,2 million unit per year. This condition shows that the demand of houses is an important need for society. On the other hand, the amount of moslem in Indonesia per 2010, according to BPS, has reached 85%. Both of these conditions show that there is a demand of houses by applying Islamic values which one of them is by using istishna’ financing scheme. But, the implementation of Islamic housing in Indonesia does not have standardized system yet in general, so that it causes some risks that need to find out. Therefore, this research is meant to find out the risk management of non-bank-house ownership financing by Sabrina Azzura. Keywords: Risk management, syariah housing, Sabrina Azzura, istishna’ financing